Charakter prawny powództwa o zmianę płci : dylematy na gruncie prawa procesowego cywilnego - Błaszczak, Łukasz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article addresses an issue of great significance, namely the legal character of actions to reassign gender. Even though the aforementioned actions have not been regulated under any legal provision, they have evolved out of judicial decisions. In this article the question of the legal character of an action to reassign gender has been settled in favor of the position that it is, in fact, an action to obtain the transformation of an existing legal right. Other procedural issues connected both with locus standi and joint participation in civil law proceedings of the respondent party have been analyzed, as well. The issue presented herein is also vital for social reasons, because it concerns a group of people categorized as transsexuals
Keywords: płeć; powództwo; zmiana; akta stanu cywilnego; dobra osobiste; legitymacja procesowa; strona procesowa